(untitled) (Research, Society and Development, 2022)
This is an article about the process of occupation of Central Brazil during the government of Getúlio Vargas, between 1930-1945, through the March to the West, which was a national policy of expansion of demographic and economic frontiers. The main objective is to describe how the State participated as an agent of expansion of national borders from 1930-to 1945, focusing on the creation of myths and advertisements that encouraged the migration of the population to the destined regions as the west. For the preparation of the work, a bibliographic review is used, as well as documental research; articles, dissertations, theses, presidential speeches, decrees, magazines, and newspapers of the time were analyzed to identify how the Brazilian State acted to promote national borders through the narrative and public policies arising from the federal government. The results found show that although the State is not the only agent responsible for the expansion of national borders, it is one of the agents involved in this process of territorial transformation, given that the category of the border is used to describe studies related to anthropic interaction with the natural environment, approaching the conflicts and constructions of myths that favor this advance over space. The conclusion demonstrates that propaganda during the Estado Novo was an important instrument for promoting the March to the West, and the consequences of this political project can be seen in the construction of the National Agricultural Colonies, construction of Goiânia, and aspects related to deforestation, migration and socio-spatial dynamics with the implementation of infrastructure and increased productivity in the regions.